Improving Students’ Vocabulary Through Mnemonic Method for Second Grade of SMP IT Nurul Iman Pesawaran - Hikmah, Miftahul Nurul; Hamdani, Zohri; Syafiq, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to improve students vocabulary mastery by using of mnemonic technique at eighth grade SMP IT Nurul Iman Pesawaran. This research used classroom action research design (CAR) to improve the students’ vocabulary mastery to support English language skills by using Mnemonic method (Harefa, 2020).The population of this research is the second grade SMP IT Nurul Iman Pesawaran, This research involves twenty students at the second gradeThis research consists of 3 cycles, the first cycle was carried out on March 5th 2024, in the first cycle the researcher made plans before entering class, such as lesson plans and learning media, then took action such as implementing the learning that had been designed, from the results of the learning the researcher carried out an evaluation then reflected in the second cycle. In this research, the researcher determined that the average score that students had to achieve was 75.00, and the results of the first cycle of learning using the mnemonic method got an average score of 61.00, because we had not reached the target, we carried out the second cycle on March 12th 2024. In the second cycle, the same as the first cycle, we reached the reflection stage and got a result of 67.75. Because we had not yet reached the target, we carried out the third cycle on March 19th 2024, by evaluating the learning that had not been optimal before, until we got an average score of 79.75. In this result, it shows an improvement students’ vocabulary mastery through mnemonic method for second grade of SMP IT Nurul Iman Pesawaran.